Design and Construction of a Sales Information System Using the Reactjs and Expressjs Frameworks: case study of Fa_al.store - Kevin Yohanes Wuryanto Wuryanto; Agung Brastama Putra; Nur Cahyo Wibowo (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Fa_al.store is a micro, small, and medium enterprise (MSME) that sells socks both online and offline. In its operational activities, the process of recording transactions and managing stock is still done manually, so the business owner experiences difficulties in monitoring product availability, assessing sales performance, and preparing periodic reports. This research aims to design and build a web-based sales information system that can facilitate transaction recording, product stock management, customer data, promotions, and presenting sales reports systematically and structured. The development of this system applies the Waterfall method, which includes the stages of needs analysis, design, implementation, and testing. On the frontend side, the ReactJS framework is used to build an interactive user interface, while the backend is developed using ExpressJS to handle business logic and communication with the database. This system is also integrated with the Midtrans payment gateway to support a secure and efficient online payment process. The results of testing using the User Acceptance Testing (UAT) method show that the system has been able to meet the functional needs of users with an acceptance rate of 94.2%, which indicates that the developed system is feasible to use and can help business actors in carrying out business processes effectively.